Influence of Solvents on The separation of Water From The bitumen Emulsions Using Alginite. - Sangar S.Ahmed (Zanco Journal of Pure and Applied Sciences, 2021)
The impact of various diluents on the removing of water from bitumen emulsions for the distillation feed (bitumen) using alginite as a demulsifier was investigated. Alginite as a natural rock is able to remove water from the bitumen emulsion. The results demonstrated that the alginite can be enhanced by adding solvents. The separation of water without adding diluents using 0.5 wt.% was about 84 %. In contrast, the addition of 2.0 mL 1-butanol can significantly improve the process resulting in water removal of 98.3 %. Furthermore, at the highest volume of hydrocarbon solvent, which was a kerosene fraction (2 mL), this yields an increase in the last water separated from 73.5 % to nearly 81.3 % in the bitumen emulsion. Consequently, the results confirmed that applying toluene, hydrocarbon solvents, and medium-chain alcohols can enhance the destabilization process when they are used together with alginite. Thereafter, changing the physical characteristics of an emulsion with the addition of diluent leads to a decrease in the viscosity of the oil phase and contributes to the coalescence of water droplets.